Metagenomic evidence for the presence of phototrophic Gemmatimonadetes bacteria in diverse environments - Zeng, Yonghui; Baumbach, Jan; Barbosa, Eudes Guilherme Vieira; Azevedo, Vasco; Zhang, Chuanlun; Koblížek, Michal (Environmental microbiology reports, 2016)
Gemmatimonadetes represents a poorly understood bacterial phylum with only a handful of cultured species. Recently, one of its few representatives, Gemmatimonas phototrophica, was found to contain purple bacterial photosynthetic reaction centres. However, almost nothing is known about the environmental distribution of phototrophic Gemmatimonadetes bacteria. To fill this gap, we took advantage of fast-growing public metagenomic databases and performed an extensive survey of metagenomes deposited into the NCBI's WGS database, the JGI's IMG webserver and the MG-RAST webserver. By employing Mg protoporphyrin IX monomethyl ester oxidative cyclase (AcsF) as a marker gene, we identified 291 AcsF fragments (24-361 amino acids long) that are closely related to G. phototrophica from 161 metagenomes originating from various habitats, including air, river waters/sediment, estuarine waters, lake waters, biofilms, plant surfaces, intertidal sediment, soils, springs and wastewater treatment plants, but none from marine waters or sediment. Based on AcsF hit counts, phototrophic Gemmatimonadetes bacteria make up 0.4-11.9% of whole phototrophic microbial communities in these habitats. Unexpectedly, an almost complete 37.9 kb long photosynthesis gene cluster with identical gene composition and arrangement to those in G. phototrophica was reconstructed from the Odense wastewater metagenome, only differing in a 7.2 kb long non-photosynthesis-gene insert. These data suggest that phototrophic Gemmatimonadetes bacteria are much more widely distributed in the environment and exhibit a higher genetic diversity than previously thought.
Keywords: multigenová rodina; Metabolic Networks and Pathways; Phototrophic Processes; metabolické sítě a dráhy; fototrofní procesy; Computational Biology; Metagenomics; metagenomika; výpočetní biologie; Bacteria; mikrobiologie životního prostředí; Environmental Microbiology; Multigene Family